(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Article is devoted to the role of the tolerance factor in the educational environment. In the article conclusions about the ethical, cognitive, humanistic, axiological, social, cultural, communicative potential of the principle of tolerance for education are made. For educational system tolerance is important as a condition of intercultural communication, disclosure of the semantic relations in society, the development of moral values, which determine the nature and impact of social, cultural and spiritual activity of man as a subject of cultural ties and social relations. Social tolerance and «methodological» point of view is considered mainly from the standpoint of the priority of spiritual, ethical component. In the article the authors drew attention to the infl uence of media culture, media technologies and the role of education in the formation of a tolerant environment, tolerant outlook. Key words: tolerance, morals, values, culture, civilization, society, spirituality, communication, education, person, globalization, media-culture